Impact of Anchoring Management Policy Riau Island Province in Indonesia - Zhuhendrik Zhuhendrik; Fitri Kurnianingsih; Okparizan Okparizan (CV. Ridwan Publisher, 2023)
The existence of waters in the Kepulauan Riau Province at the crossing of international shipping relations brings Indonesia various opportunities for developing valuable environmental and marine services. This research aims to make efforts and alternatives to the optimization strategy of anchorage activities in the Kepulauan Riau Province to manage the potential for environmental and marine services to increase local revenue in the border region. The research method used descriptive qualitative by using secondary data derived from documents, journals, books, websites and other supporting data that focused on analyzing the anchorage development strategy in the waters of the Riau Island Province. The data analysis technique used a data source triangulation approach. The findings show that the impact which occurs in the development of anchorage has three options for optimizing strategies during the COVID-19 pandemic; firstly, maximizing ship guiding and towing services in the Malacca Strait and Singapore Strait, secondly, ship guiding and towing services at TUKS and TERSUS must be given the authority to the Regional Owned Enterprises (BUMD), namely P.T. Pelabuhan Kepri; and thirdly, the importance of controlling environmental impacts on anchorage activities in the Kepulauan Riau Province. Afterwards, the researcher also provides an alternative to implementing the Penta-helix concept as a form of monitoring anchors in the waters of the Kepulauan Riau Province.